Prevalence of adverse childhood experiences and effect on outcomes in bariatric surgery patients: a systematic review and meta-analysis - Paul, Cinara; Inhoffen, Johannes; Friederich, Hans-Christoph; Hartmann, Mechthild; Wild, Beate (Surgery for obesity and related diseases, 2023)
Adverse childhood experiences (ACEs) are defined as childhood maltreatment (sexual, physical, and emotional abuse and neglect) and other childhood traumatic experiences. Published prevalence estimates for ACEs in bariatric samples vary greatly and evidence on the association between ACEs and bariatric surgery weight loss and psychosocial outcomes is inconclusive. A systematic literature search on PubMed/Medline, PsycInfo, Web of Science, CINAHL (Cumulative Index of Nursing and Allied Health Literature), and Open Grey for studies published until August 30, 2021, yielded 21 publications for qualitative synthesis: 20 reporting on prevalence of ACEs in bariatric surgery candidates and patients, and 10 on the association of ACEs with outcomes. In meta-analysis, overall moderate to high heterogeneity was observed for prevalence estimates and moderate heterogeneity was observed for associations. Prevalence estimate for at least 1 form of ACEs (6 studies, n = 1368 patients) was 51% (95% confidence interval [CI]: 32%-70%). Effect size (Hedge’s g) for the difference between the groups of patients reporting any or a high number of ACEs versus no or a low number of ACEs was calculated from means, standard deviations and group size, or P values. Based on 7 studies (n = 946 patients), the association between ACEs and weight loss was not significant (Hedge’s g = -.15 [95% CI: -.38 to .09]; I2 = 53%), regardless of short- or long-term follow-up (P = .413) and the proportion of patients in each study receiving Roux-en-Y gastric bypass (RYGB) (β = .0005, P = .868). Preliminary findings based on 3 short- and long-term studies (n = 414 patients) showed that ACEs were significantly (P = .001) associated with higher postoperative depressive symptoms (Hedge’s g = .50 [95% CI: .22-.78]; I2 = 36%). Associations between ACEs and other psychosocial outcomes such as eating pathology were reported narratively. There is a need for additional long-term studies using validated assessment tools for ACEs to evaluate the effect of ACEs on weight and psychosocial outcomes after bariatric surgery.
Online verfügbar:12. September 2022, Artikelversion: 25. Januar 2023
Gesehen am 17.08.2023